Analysis of leukocyte membrane protein interactions using protein microarrays (BioMed Central, 2005)
Background: Protein microarrays represent an emerging class of proteomic tools to investigate multiple protein-protein interactions in parallel. A sufficient proportion of immobilized proteins must maintain an active conformation and an orientation that allows for the sensitive and specific detection of antibody and ligand binding. In order to establish protein array technology for the characterization of the weak interactions between leukocyte membrane proteins, we selected the human leukocyte membrane protein CD200 (OX2) and its cell surface receptor (hCD200R) as a model system. As antibody-antigen reactions are generally of higher affinity than receptor-ligand binding, we first analyzed the reactivity of monoclonal antibodies (mAb) to normal and mutant forms of immobilized CD200R. Results: Fluorescently labelled mAb DX147, DX136 and OX108 were specifically reactive with immobilized recombinant hCD200R extracellular region, over a range of 0.1-40 µg ml-1 corresponding to a limit of sensitivity of 0.01-0.05 femtomol per spot. Orientating hCD200R using capture antibodies, showed that DX147 reacts with an epitope spatially distinct from the more closely related DX136 and OX108 epitopes. A panel of soluble recombinant proteins with mutations in hCD200R domain 1 produced by transiently transfected cells, was arrayed directly without purification and screened for binding to the three mAb. Several showed decreased binding to the blocking mAb DX136 and OX108, suggesting close proximity of these epitopes to the CD200 binding site. Binding of hCD200 to directly immobilized rat, mouse, and hCD200R was achieved with multimeric ligands, in the form of biotinylated-hCD200 coupled to FITClabelled avidin coated beads. Conclusion: We have achieved sensitive, specific and reproducible detection of immobilized CD200R with different antibodies and mapped antigenic epitopes for two mAb in the vicinity of 3 the ligand binding site using protein microarrays. We also detected CD200 binding to its receptor, a low affinity interaction, using beads presenting multivalent ligands. Our results demonstrate the quantitative aspects of protein arrays and their potential use in detecting simultaneously multiple protein-protein interactions and in particular the weak interactions found between leukocyte membrane proteins.